Managing International Business in Relation Based versus Rule-Based Countries - Shaomin, Li (Business Expert, 2012)
This book summarizes the research in the past 10 years on how different governance environments at the national level affect business operations and management. Its primary audience includes executives who manage business across borders. Readers interested in international political economy and comparative culture may also fi nd it intriguing. A country’s governance environment includes the political, economic, and social systems that facilitate or constrain the way fi rms and individuals govern their social exchanges and business activities. This book distinguishes and examines the two major governance environments in the world, the rule-based system (conventionally called the “Western way”) and the relation-based system (the “Asian way”), and demonstrates that the Asian way does not come from cultural heritage, but rather it is a result of the particular stage of political and economic development in which public rules are not fair and effective. The author argues that contrary to the conventional view that dismisses the relation-based way as backward, it may be effi cient under certain conditions. This book further shows that the success of the relation-based way is not primarily based on the family but on a more extended informal social network beyond the family. This book discusses how business operations and investments are protected and managed under relation-based governance and demonstrates that some major management diffi culties and investment failures in international business that were previously puzzling can now be clearly explained by the lack of understanding of the key features of relation-based governance. This book concludes with discussions on the transition from relation-based to rule-based governance that many relation-based countries are going through, the special challenges of the transition, and how businesses and societies may successfully navigate through such a transition.